Pendekatan Anova dalam Menentukan Keputusan Investasi pada Perusahaan Perkebunan di Indonesia - Suyono Suyono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The growth of companies in the plantation sector, it can be assumed that the plantation sector in Indonesia is still classified as a potential. so that it can be a benchmark for many investors in investing in the plantation sector. One of the indicators in investing can be seen from the financial performance, the company's stock price and the exchange rate. The study found that there were differences between financial performance, stock prices and the exchange rate of plantation sector companies listed on the Indonesia Stock Exchange during 2015-2018. This research was conducted as a measure of investors to invest in companies. This research method uses a quantitative approach because to find out and analyze differences in financial performance, stock prices and macroeconomic variables in plantation companies with a different approach and test the correctness of existing theories. While the hypothesis test used is the Analysis of Variance (ANOVA) method. The results showed there was no difference between the stock price and the exchange rate (KURS) of the company. Whereas the financial performance variable (ROA) points to a significant difference between the financial performance of one plantation company from another during the priod 2015-2018. Keywords: Stock Prices, Financial Performance (ROA), Macroeconomics (KURS)